Mastering Nmap - Chantzis, Fotis (Packt Publishing, 2017)
"You will learn how to use this tool to implement a wide variety of practical tasks related to pentesting and network monitoring. The tutorial will start with installation techniques and then explain Nmap fundamentals. Moving on, we will cover the advanced functionalities of Nmap Scripting Engine (NSE) such as libraries, scripts, APIs, and so on. You will be able to perform custom tasks, the fundamentals of Lua programming, scanning mail servers, scanning databases, windows machines, SCADA systems, and large networks."--Resource description page